Implementation of the Website-Based Game “Blooket.com” as a Medium to Enhance Vocabulary Mastery in German Language Learning at SMA Laboratorium UM - Puspita, Arsita Angel; Sobara, Iwa (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
This research aims to describe the application of games based on the Blooket.com website as a medium for practicing mastery of German vocabulary and describe students’ responses in practicing mastery of German vocabulary after the games on the website are implemented. The method used in this research is descriptive qualitative using observation sheets, questionnaires and tests. The results of this study indicate that Blooket.com can be used as an alternative media in learning German to train students' vocabulary mastery. Apart from that, website-based games can also provide an enthusiastic, enthusiastic effect, and can attract students. Therefore, this website can be used as an alternative game media that can be used to practice vocabulary mastery in further German language learning.